Skrining Aktivitas Antibakteri Ekstrak Etanol 70% Sepuluh Daun Tanaman Terhadap Klebsiella Pneumoniae - Nurul Qolbi; Ratna Yuliani (Universitas Muhammadiyah Surakarta, 2018)
Klebsiella pneumoniae causes several diseases such as chronic obstructive lung disease and community pneumonia. The antibiotics used for treating the infectious diseases cause several side effects. Therefore, alternative medicines which have minimal side effects are needed. This research aimed to investigate antibacterial activity of ten ethanolic extract of leaves against K. pneumoniae, identify compounds and active compounds in extract which has the highest antibacterial activity. Compounds in leaves were extracted using 70% ethanol with maceration method. The disk diffusion method was used for screening antibacterial activity against K. pneumoniae. The identification of group of compounds in extract with the largest inhibitory zone diameter was done using Thin Layer Chromatography (TLC) and bioautographic test was performed to determine the active compounds. The results of antibacterial activity screening tests showed that all extracts have antibacterial activity except bamboo leaf extract. Breadfruit extract (Artocarpus altilis) has the highest antibacterial activity with diameter of inhibition zone of 18,33 ± 5,57 mm. Breadfruit extract contains tannin, polyphenol, alkaloid, terpenoid, saponin, and the active antibacterial compounds were terpenoid and saponin.